A comparison of organophosphate degradation genes and bioremediation applications. Issue 6 (16th September 2013) - Iyer, Rupa; Iken, Brian; Damania, Ashish
Abstract Organophosphates (OPs) form the bulk of pesticides that are currently in use around the world accounting for more than 30% of the world market. They also form the core for many nerve‐based warfare agents including sarin and soman. The widespread use and the resultant build‐up of OP pesticides and chemical nerve agents has led to the development of major health problems due to their extremely toxic interaction with any biological system that encounters them. Growing concern over the accumulation of OP compounds in our food products, in the soils from which they are harvested and in wastewater run‐off has fuelled a growing interest in microbial biotechnology that provides cheap, efficient OP detoxification to supplement expensive chemical methods. In this article, we review the current state of knowledge of OP pesticide and chemical agent degradation and attempt to clarify confusion over identification and nomenclature of two major families of OP‐degrading enzymes through a comparison of their structure and function. The isolation, characterization, utilization and manipulation of the major detoxifying enzymes and the molecular basis of degradation of OP pesticides and chemical nerve agents are discussed as well as the achievements and technological advancements made towards the bioremediation of such compounds.